'Now that's the feedback I want!' Students' reactions to feedback on graded work and what they do with it. Issue 4 (19th May 2017) - Pitt, Edd; Norton, Lin
Abstract : Since the introduction of the National Student Survey (NSS) in 2005, like many other institutions, the university where this study took place has expended substantial effort in improving the quality of feedback to students. However, despite much research, changes in pedagogical approaches and shifts in conceptual understanding related to feedback practice, assessment and feedback still receive the lowest satisfaction ratings in the NSS. Lecturers are discouraged when students fail to take note of their feedback, or sometimes do not collect assignments that have been marked. Understanding why feedback is not always acted upon remains an important area for researchers. This paper reports on an in-depth interview study with 14 final year undergraduates, reflecting on their perceptions of feedback written on marked assignments, by selecting examples of what they considered to be 'good' and 'bad' work. Findings suggested that emotional reactions play a significant part in determining how students will act on the feedback they receive, and the concept of 'emotional backwash' is introduced.